THE RELATIONSHIP OF EXCLUSIVE BREASTFEEDING AND GENDER WITH NUTRITIONAL STATUS OF INFANTS AGED 7-12 MONTH AT PUBLIC HEALTH CENTER OF PARIGI, MUNA REGENCY OF SOUTHEAST SULAWESI PROVINCE - Aprianti Wayan (Stikes Graha Edukasi Makassar, 2019)
Introduction: Nutritional status is a body's state as a result of eating and nutrients utilization. Exclusive breastfeeding is breast milk given to infants from newborn to 6 months without complementary foods and pralacteal. Method: The research uses analytical design with cross-sectional approach. The population was all breastfeeding mothers who had infant aged 7-12 month at the Public Health Center of Parigi of Muna regency. The sample used is 74 infants aged 7-12 months at the Public Health Center of Parigi, Muna regency of Southeast Sulawesi Province. Result: Research obtained that 35 infants exclusively breastfed, 62 infants (83.8%) had good nutrition and 12 infants (16.2%) had less nutrition. Less nutritional status and not-exclusively breastfed is 10 (28.6%) and 25 (71.4%), good nutrition and exclusive breastfeeding 2 (5.1%) and 37 (94.9%). Based on cross-sectional test obtained Z-value - 2.746 with p-value 0.006 <a (0.05). Conclusion: There is a significant relationship of nutritional status of infants aged 7-12 months who given exclusive breastfeeding and gender for babies at the Public Health Center of Parigi, Muna regency of Southeast Sulawesi Province.